YouTube as a Source of Information on Pulmonary Rehabilitation for COPD Patients - Bilgehan Kolutek Ay; Hatice Şahin (Düzce Tıp Fakültesi Dergisi)
Aim: YouTube is increasingly being used as a platform for accessing health-related information, including diseases and treatments. This study aimed to evaluate the reliability and quality of YouTube video content on pulmonary rehabilitation in chronic obstructive pulmonary disease (COPD) patients and determine whether YouTube is a reliable source of information.Material and Methods: A total of 60 videos were included in the study by searching on YouTube with the keywords "pulmonary rehabilitation", "COPD exercises", and "breathing exercises". The quality, reliability, and accuracy of the videos were assessed using the Global Quality Scale (GQS), the modified DISCERN (mDISCERN) score, and the Journal of the American Medical Association (JAMA) scoring system, respectively. Data such as video duration, view rate, uploader, and narrator were analyzed and used to compare quality and reliability.Results: None of the videos had a full JAMA score. A statistically significant relationship was found between view rate and low-to-moderate quality videos (p